Cancer Stem Cell: Target Baru Obat Antikanker - DANNY HALIM; TONO DJUWANTONO; TRI HANGGONO AHMAD (Indonesian Journal of Cancer, 2010)
Relaps, resistance and metastasis has become prominent problems that oncologists and cancer patients have to dealt with. Various studies have been done previously concluded that there are a subpopulation of cancer cells, identified as cancer stem cell, most likely to be the cause of relaps, resistance and metastasis of cancer. Cancer stem cell is a subpopulation of cancer cells that possess tumorigenicity, hence it can initiate the growth of tumor. Cancer stem cell has been suspected to be originated from normal stem cells reside in mature tissues, or from progenitor cells that gone through some series of alterations on its characteristics, including mutagenic and non-mutagenic changes. As seen in normal stem cells, cancer stem cell is also oftenly found in its inactive state. Therefore, cancer stem cell is not affected when it treated with many chemotherapeutic agents that are targeting cancer cells that proliferate extensively. Eventually, this event leads to the incidence of cancer relaps on cancer patients who already had series of cancer therapy. Based on this knowledge, it can be concluded that the only absolute way to overcome the incidence of metastasis, resistance and relaps on cancer patients, is to targeting cancer stem cell. Therefore, optimization on protocols of cancer stem cell identification and isolation strived continously. Some molecular markers that are oftenly used as a standard on cancer stem cell isolation are CD34, CD44 and CD133. In line with that, isolation methods that are based on sphere formation and the absorption of coloring dye could also be done to obtain cancer stem cell population. This review article would like to explain the nature of cancer stem cell existence, the pathology underlies its formation, characteristics and identification techniques that are commonly used, and challenges that have to be faced by scientists and physicians in order to optimize the application of cancer stem cell theory for the progress of science and patients sake.